Analisis Standard Operating Procedure (SOP) Tes Keterampilan Teknik Passing pada Bolabasket - Nanda Hendryatma; Himawan Wismanadi; Achmad Widodo; Hijrin Fithroni (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Basketball requires mastery of fundamental techniques to enhance effective and efficient playing skills. One of these fundamental techniques is the passing technique. It is not easy for athletes to master proper passing techniques, hence the necessity for training in accordance with the applicable SOP (Standard Operating Procedure). This research aims to determine whether the form of passing technique training meets the SOP in improving athletes' passing skills. The study was conducted quantitatively using the 4D (Four-D Models) development method. The research results include the development of a passing test involving chest passes performed by two stationary athletes over a duration of 30 seconds with a total of 36 athletes. The results of the analysis showed that 55.6% got the sufficient category, 30.6% got the less category and 13.9% got the very less category. As for the good and excellent categories, there are none or 0%. So it is concluded that the development of passing tests owned by athletes is still somewhat lacking, characterized by the absence of athletes who are classified in the good or excellent category.